Passivity-Based Control for Small Hydro-Power Generation With PMSG and VSC - Walter Gil-Gonzalez; Alejandro Garces; Olav B. Fosso (IEEE Access, 2020)
This paper presents a passivity-based control method for a small hydro-power system that consists of a permanent magnet synchronous generator (PSMG) connected to the grid through a back-to-back converter. Nonlinear models of the hydraulic, mechanical, and electrical parts of the small hydro-power system are considered. Two approaches in the realm of passivity-based control are implemented, namely, standard passivity-based control and PI-passive. These controls consider the intrinsic characteristics of the model, which has a port-Hamiltonian (pH) structure with a small hydro-power system in open-loop. The purpose is to design a control law with passive output which ensures asymptotic stability for closed-loop operation in the sense of Lyapunov's theory. The paper is practically oriented, and hence, the proposed controllers are tested and compared with a conventional approach, in a 13.2 kV distribution feeder. The proposed controllers have been assessed and compared with a classical PI controller considering steady state and transient behaviors in small hydro-power plants (SHPs). Simulation results show that the proposed methodology guarantees stability and offers better dynamical performance.